2012
DOI: 10.1007/s00404-012-2643-5
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cigarette smoking on a population of infertile men and women

Abstract: Cigarette smoking is associated with damaging effects on sperm parameters in infertile men and with ovarian reserve alteration in infertile women, as reflected by reduced AFC and increased FSH levels. Every smoker should be encouraged to stop smoking to prevent the damage of the toxins contained in cigarette smoking and preserve their own reproductive potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 32 publications
2
39
1
2
Order By: Relevance
“…91,92 Pregnancy-related smoking consequences include infertility, spontaneous abortion, preterm delivery, and perinatal mortality. 9,89 These data again highlight the importance of measuring hormone levels when conducting smoking research in women. Using information about the association of the menstrual cycle to smoking to improve cessation outcomes for women may also have important consequences on improving menstrual cycle health.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…91,92 Pregnancy-related smoking consequences include infertility, spontaneous abortion, preterm delivery, and perinatal mortality. 9,89 These data again highlight the importance of measuring hormone levels when conducting smoking research in women. Using information about the association of the menstrual cycle to smoking to improve cessation outcomes for women may also have important consequences on improving menstrual cycle health.…”
mentioning
confidence: 94%
“…Smoking in women is associated with dysmenorrhea and menstrual irregularity 9,82 and altered ovarian cycle and hormone levels. 83,84 Compared to female nonsmokers, female smokers demonstrate changes in estrogen metabolism and lower circulating estrogen, 85,86 a shorter reproductive lifespan, 9,87,88 lower ovarian reserve, 89,90 and quicker entry into all stages of the menopausal transition. 91,92 Pregnancy-related smoking consequences include infertility, spontaneous abortion, preterm delivery, and perinatal mortality.…”
mentioning
confidence: 99%
“…Other studies did not find a significant alteration of conventional semen parameters in smokers [27,28]. Some others showed mixed results [29,30]. Soares and Melo [31] reviewed the literature on the relation between cigarette smoking and reproductive function and indicated that cigarette smoking has a negative effect on the male and female reproductive function.…”
Section: Introductionmentioning
confidence: 98%
“…However, smoking cessation has been associated with a decrease in testosterone levels [47,48]. Furthermore, when comparing sperm parameters between smokers and non-smokers, some studies showed a lower sperm concentration [49,50,51,52], lower total sperm count [50,51,52,53] and lower semen volume [51,52,54] in current smokers, while other studies demonstrated no effects on these parameters [55,56]. Recent in vitro work has shown that some of the compounds present in cigarettes are capable of decreasing AR activity [57], possibly by inhibition of DNA binding on androgen-responsive elements in target genes [58].…”
Section: Smokingmentioning
confidence: 99%